2016
DOI: 10.1007/s00592-015-0828-7
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of young infants presenting neonatal diabetes mellitus with continuous subcutaneous insulin infusion before genetic diagnosis

Abstract: During the neonatal period, the use of CSII therapy is safe, more physiological, accurate and easier for the insulin administration management. Furthermore, CSII therapy is safe during the switch of therapy from insulin to glibenclamide for infants with permanent neonatal diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Insulin delivery in small infants is a challenge as the requirement is small, absorption is variable, the risk of dose error due to unavailability of ready-made diluted insulin is high and there are limited data for dilution of commercially available insulin preparations [15,16]. Although insulin pump therapy appears to be effective at this age group [16][17][18] only 36% of participants used pump for NDM, possibly due to limited resources in some countries. Interestingly, only 58% of surveyed physicians used insulin analogues, with more pediatric endocrinologists in favour of its use than pediatricians with interest in diabetes (67% vs 37%; p = 0.011).…”
Section: Discussionmentioning
confidence: 99%
“…Insulin delivery in small infants is a challenge as the requirement is small, absorption is variable, the risk of dose error due to unavailability of ready-made diluted insulin is high and there are limited data for dilution of commercially available insulin preparations [15,16]. Although insulin pump therapy appears to be effective at this age group [16][17][18] only 36% of participants used pump for NDM, possibly due to limited resources in some countries. Interestingly, only 58% of surveyed physicians used insulin analogues, with more pediatric endocrinologists in favour of its use than pediatricians with interest in diabetes (67% vs 37%; p = 0.011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, along with the literature [21], the present survey showed that CSII is also used more and more frequently in young childhood. On the other hand a conventional insulin therapy using pre-mixed insulin, which was relatively common about 20 years ago, is only seldom used today [21][22][23][24][25]. Reasons for these tendencies include modern insulin pumps [26,27], new insulin preparations, and innovative technical procedures (including continuous glucose monitoring) [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…While waiting for the genetic results, the medical treatment is the same and must target first an appropriate caloric intake to improve the nutritional status of these babies and insulin administration for an adequate blood sugar control (4, 5). Insulin is absolutely required and should be started as soon as the diagnosis was made.…”
Section: Discussionmentioning
confidence: 99%